Studies on protein content of cestode Cotugnia and its host Gallus gallus domesticus - Nanware, S S; Nazneen, Uzma; Bhure, D B; Garad, V B (Journal of Experimental Sciences, 2012)
The present study deals with the protein content in cestode parasite Cotugnia digonopora and its host tissue i.e. normal and infected intestinal tissue of Gallus gallus domesticus. The result obtained an amount of protein content in the present study indicates that the amount of proteins present in cestode parasites is lower as compared to protein present in infected intestine as well as in normal intestine.